Evidence‐based consumer choice: a case study in colorectal cancer screening - Glenn Salkeld; Michael Solomon; Leonie Short; Mandy Ryan; Jeanette E. Ward (Elsevier, 2003)
Abstract Objectives:To elicit community preferences for colorectal cancer (CRC) screening by faecal occult blood test (FOBT) using discrete choice modeling (DCM). To provide policymakers with information that would assist them in designing the future national screening program. Methods:301 participants in central Sydney, aged 50 to 70 years, at 'average' risk of CRC, participated in a face‐to‐face discrete choice study interview in which screening profiles were posed to derive estimates for preferences for CRC FOBT screening. Results:Three characteristics were varied in our screening profiles, namely: benefit (CRC deaths prevented); potential harm (false positive induced colonoscopy); and notification policy (of test result). Ninety‐four respondents (32%) did not trade off CRC deaths prevented for any reduction in harms. Twelve per cent always chose no screening. The remaining 56% traded benefits and harms. These latter respondents (n=164) were willing to accept 853 (false positive induced) colonoscopies for one CRC death prevented. Conclusions:While survival was all that mattered for just over one‐third of the sample and 12% would choose no screening, the remaining individuals were prepared to trade CRC deaths prevented against other characteristics. CRC screening will not receive unqualified community support, irrespective of harms. Implications:In any future national CRC screening program, consideration of these insights about community assessment of benefits, harms, costs and other characteristics of CRC screening is warranted.